The relationship between the levels of intercultural sensitivity and cultural intelligence in nurses - Hülya Firat Kiliç; Cevheroglu, Seda; İncihan Kahraman (Nursing and Health Sciences Journal (NHSJ), 2025)
The holistic approach in nursing requires consideration of the cultures of patients receiving healthcare. Every individual has the right to receive culturally appropriate nursing care, which is not a privilege but a human right. This study was utilized to determine the relationship between intercultural sensitivity and cultural intelligence in nurses. The study population consisted of 741 nurses working at state hospitals in Northern Cyprus. A stratified sampling method was used to recruit 300 participants. A descriptive information form, intercultural sensitivity scale, and cultural intelligence scale were used for data collection. The mean intercultural sensitivity scale and cultural intelligence scale scores were 76.20±8.92 and 64.72±14.2, respectively. There was a positive and statistically significant relationship between the intercultural sensitivity scale scores and the scores obtained from the cultural intelligence scale and its subscales (p<0.05). Squared partial correlation showed that the place of residence had the highest impact on intercultural sensitivity. The levels of intercultural sensitivity were moderate, but cultural intelligence was low. There was a positive relationship between intercultural sensitivity and cultural intelligence and its subscales. Therefore, we recommend planning in-service training to improve the levels of cultural intelligence and intercultural sensitivity so that nurses can provide high-quality nursing care, avoid discrimination, and establish therapeutic relationships with people with different cultural backgrounds, whose numbers have increased as a result of factors, such as migration or health tourism.